Joycean Pastiches and other literary devises in "La caza salvaje" de Jon Juaristi - Morales Ladrón, Marisol (Estudios Ingleses de la Universidad Complutense, 2012)
The first novel by essayist and poet Jon Juaristi, La caza salvaje, was awarded the Premio Azorín in 2007. Deeply intellectual and erudite, the narrative opened parodying the beginning of one of the most emblematic works in XXth-century literature, James Joyce’s Ulysses. Its aesthetic hybridity, together with its transgression of literary and ideological boundaries, allowed Juaristi to offer a renewed version of Basque nationalism. However, my contention in this article is that Joycean literary echoes, along with his ideological position as regards Irish nationalist leaders, provided Juaristi with more than mere coincidental resonances. Bearing these assumptions in mind, the present study stems from the analysis of Joyce’s aesthetics as a source of inspiration for La caza salvaje, in order to further deepen into the meaning that Joyce’s oeuvre acquires in light of Juaristi’s complete production.